Changes in peptidergic nerves in the atrioventricular valves of streptozotocin-induced diabetic rats: A confocal microscopy study - Kumar, S.-D. (2012)
10.1002/(SICI)1097-0185(20000301)258:3<277::AID-AR7>3.0.CO;2-U